Green Supply Chain Management, Investment Recovery, Competitiveness, and Organizational Performance.: A Case of Manufacturing Firms in Indonesia - Sudarmaji, Heri; Nurlaela, Luthfiyah; Hariadi, Eko (International Journal of Supply Chain Management, 2020)
The main purpose of the current study is to examine the impact of the green supply chain management, investment recovery, competitiveness, on organizational Performance. This research work is based on the acknowledgment of findings of GrSCM activities by examining the three various kinds of outcomes regarding performance. The present study has adopted the survey based methodology and data is collected with the aid of an adapted questionnaire. A total of 420 questionnaire were distributed among the manufacturing firms in Indonesia. Out of these the 307 questionnaire were usable for analysis. The research conducted that included survey of medium-scale textile and large-scale textile companies both are included, so according to this survey it was estimated that in the textile industry of Indonesia the Indonesian manufacturers are reactive to the buyer’s requirement towards the environmental issues and hence, it became more of market concern. The stress from the small foreign companies and buyers is particularly very less: it forces the Indonesian textile industry to adjust themselves on a further urgent basis. the research work assumed a more general approach to its theoretical development of a model with a perception that participants of the supply chain collaborated and would depend on one another. These activities encourage the organizations to find advantages of high-level performance in the long-term as compared to the short run.